Perspectives of Contemporary Muamalah Jurisprudence Law on Buying and Selling "claw" on the TikTok Application - Arifah, Arifah (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Technological developments make changes to the buying and selling system. One of the most popular systems is buying and selling claws on TikTokshop. The purpose of this study is to determine whether buying and selling "claws" is in accordance with Islamic economic law or not. The research method is literature research. The results of the stu dy indicate that there are three problems that exist in the sale and purchase of claws, namely the type of goods, the quality and quantity of the goods, and how to take the object of the contract. In line with the permissibility of buying and selling online using a salam contract, the sale and purchase of claws must also follow the terms and conditions of the sale and purchase of salam because it is done online. In the sale and purchase of greetings, the object of the contract must be clear about the shape, size, quantity, and quality agreed at the beginning of the contract. So, based on the research results, the sale and purchase of claws contains elements of gharar (unclear) and maisir (chance) because the object of the contract depends on the seller's head, which is not known how the quantity and quality will be obtained by the buyer.